PENGARUH PEMBERIAN REMUNERASI TERHADAP KINERJA ANGGOTA POLRI SATUAN RESERSE DAN KRIMINAL KEPOLISIAN RESORT TEBO - Susanti, Desti; Novriansyah, Yudhi; Yeni, Misra (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The objectives to be achieved in this study is to know influence of remuneration to POLRI officer performance in Police Resort of Tebo. Quantitative descriptive research survey approach. Respondents as many as 33 Polices officer at Detective and Crime Unit of Kepolisian Resort Tebo. In this research uses the sample withdrawal Total Sampling. The results showed: (1) t test > t table as number as 9.272 > 2.040, and H0 rejected and H1 be accepted. It’s mean Remuneration variable has influence to performance of Police Officer at at Detective and Crime Unit of Kepolisin Resort Tebo. Data Analysis use simple correlation model resulted cooficient determinant (R2) 0,735 or 73, 5%. To show ability of independent variable (remunation) explained dependent variable (performance). while 22,5 % influent by others variable.